(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The article provides information on the export of agricultural products to different countries. Currently, we are faced with the task of abandoning the monopoly on cotton and introducing a new approach to its use. These are the issues discussed in the article, the complete processing of raw cotton before receiving finished cotton products in textile production in the so-called clusters and selling it for export. This increases the importance and importance of agricultural exports in our country. Along with this, attention is paid to the process of growing grain, fruits and vegetables, grapes, which are well exported both to the CIS countries and abroad. We have agreed with Russia and other countries to implement a project to create an Agro-Express for the transportation of agricultural products. An increase of 5% is planned in this area.